Leisure activities, well being and sense of community of the elders in the coastal community of Lapaz-Tubog, Hamtic, Antique - Lamprea, Jessy Lyn C.
This is a descriptive study aimed to determine the leisure activities, well-being and sense of community of the elders in the coastal community Lapaz-Tubog, Hamtic, Antique., Forty(40) elders, thirteen (13) males and twenty-seven (27) females were chosen through purposive sampling as respondents. Leisure Activities Questionnaire, Subjective Well-Being Invemtory and Sense of community Index were utilized to gather the necessary data. Findings of the study that the elders generally prefer less physically demanding leisure activities. health and socio-economic level are assumed to influence their choice of activities. health and socioeconomic level are assumed to influence their choice of activities. Despite poverty and the toll of old age, the respondents are moderately satisfied with their lives. The study also found the respondents as having high sense of community. years of residence, neighborhood relations and characteristics of neighborhood (homogenous population and physical bounary) are some of the factors that may have contributed to their sense of community.